Cross-Domain Transfer Learning for Robust Pattern Detection in Evolving Digital Identity Ecosystems - Suman Kumar Sanjeev Prasanna (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The rapid evolution of digital identity platforms often results in a significant distribution shift between historical training data and emerging operational environments. Traditional detection models struggle with this domain gap, leading to degraded performance when deployed across heterogeneous platforms. This research introduces a Cross-Domain Transfer Learning (CDTL) framework designed to enhance the generalizability of identity anomaly detectors. The approach utilizes Adversarial Domain Adaptation (ADA) to align the feature distributions of a labeled source domain (historical data) with an unlabeled target domain (live operational data) within a shared latent space. By incorporating a consistency-regularized fine-tuning strategy, the framework preserves critical identity-authoring signals while discarding domain-specific artifacts that contribute to model drift. The study further explores the use of mid-level attribute transfer to bootstrap detection performance in data-scarce environments. Experimental results across multiple cross-institutional identity datasets demonstrate that the proposed CDTL framework achieves a 15% improvement in detection accuracy on target domains compared to non-adaptive baselines. These findings establish transfer learning as a critical methodology for maintaining the integrity of identity verification systems in the face of rapid technological and behavioral evolution.